Fostering Collaborative Growth: Strategic Communication and Capacity Building in PEKKA Women’s Entrepreneurial Projects - Juwita, Rina; Rohmah, Ainun Ni’matu; Arsyad, Annisa Wahyuni (Indonesian Journal of Advanced Research, 2025)
Strategic communication and focused capacity-building initiatives are essential for collaborative progress in underrepresented areas. This research investigates the function of strategic communication in promoting cooperation and augmenting the entrepreneurial capabilities of women heads of households (PEKKA) in Samarinda, Indonesia, using the MomPreneurs program. The project tackles critical obstacles, such as restricted access to technology, insufficient digital literacy, and ineffective marketing techniques. The program employs a participative method to include technical support, digital marketing training, and mentorship for the development of entrepreneurial abilities. Study indicates that strategic communication methods, including storytelling and peer networking, significantly improve information dissemination and collaborative problem-solving among participants. Capacity-building initiatives, including practical training and digital marketing seminars, led to a 20-35% enhancement in productivity and income among participant groups. Moreover, promoting cooperation via group-oriented business endeavors reinforced community links and elevated individual drive. This study emphasizes the significant effect of integrating strategic communication with focused skill development to empower underprivileged women. The results enhance the discussion on social entrepreneurship and community empowerment by illustrating how communication-focused projects may stimulate sustained economic development. The study highlights the need for scalable solutions that include communication tactics and capacity-building to tackle structural inequities in emerging countries.